Acellular Dermal Matrix as an Adjunct Material in Cleft Le Fort I Osteotomies. Issue 1 (January 2017) - Susarla, Srinivas M.; MacIsaac, Zoe M.; Swanson, Edward; Davidson, Edward; Kumar, Anand
Abstract : Purpose: To evaluate the use of acellular dermal matrix in the management of nasal lining deficiency at the time of Le Fort I osteotomy. Methods: This was a retrospective cohort study of patients with residual/recurrent oronasal fistulae who underwent Le Fort I osteotomy. In instances where there was an inadequate volume of nasal mucosa for tension-free closure or for defects >1 cm in width, the acellular dermal matrix was used for augmentation. Demographic and cleft-related factors were recorded. Complications (recurrent fistula, infection, seroma, and wound dehiscence) were recorded. Results: Over the 3-year period, the authors used acellular dermal matrix to augment nasal lining in 8 subjects. The sample's mean age was 18.7 ± 3.1 years; 5 subjects were male. Six patients had bilateral cleft defects. The mean follow-up time was 20.2 ± 3.2 years. There were no episodes of infection, seroma, wound dehiscence, or recurrent fistula. Conclusion: Acellular dermal matrix is a useful adjunct for managing nasal lining deficiency at the time of Le Fort I osteotomy. There were no episodes of bone graft extrusion, infection, tooth loss, or bone graft loss. The Enemark scores improved significantly across both subsets ( P <0.001). There was 1 recurrent fistula in the allograft bone alone group. Residual alveolar clefts and oronasal fistulae can be successfully managed at the time of Le Fort I osteotomy using allograft bone and acellular dermal matrix.